2006
DOI: 10.1088/0022-3727/39/5/s13
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the phase diagram of magnetic shape memory Heusler alloys

Abstract: We have modelled the phase diagram of magnetic shape memory alloys of the Heusler type by using the phenomenological Ginzburg–Landau theory. When fixing the parameters by realistic values taken from experiment we are able to reproduce most details of, for example, the phase diagram of Ni2+xMn1−xGa in the (T, x) plane. We present the results of ab initio calculations of the electronic and phonon properties of several ferromagnetic Heusler alloys, which allow one to characterize the structural changes associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
240
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(260 citation statements)
references
References 130 publications
18
240
1
1
Order By: Relevance
“…The martensitic transition is driven by phonon instabilities in the transverse TA 2 phonon branch ͓͑110͔ propagation and ͓110͔ polarization͒. 22,23 Recent ab initio calculations for cubic Ni 2 MnIn have shown that increasing the magnetization due to an external field favors the cubic structure and leads to a gradual vanishing of the phonon instability 24 due to the coupling between vibrational and magnetic degrees of freedom. This effect results in a marked decrease of the martensitic transition temperature with increasing field that enables to induce the transition by the application of a field at a temperature close to the zero field transition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The martensitic transition is driven by phonon instabilities in the transverse TA 2 phonon branch ͓͑110͔ propagation and ͓110͔ polarization͒. 22,23 Recent ab initio calculations for cubic Ni 2 MnIn have shown that increasing the magnetization due to an external field favors the cubic structure and leads to a gradual vanishing of the phonon instability 24 due to the coupling between vibrational and magnetic degrees of freedom. This effect results in a marked decrease of the martensitic transition temperature with increasing field that enables to induce the transition by the application of a field at a temperature close to the zero field transition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Since Ni 2 MnGa is known to show pronounced Fermi-surface nesting behavior and large phonon softening, 18,23,24 the question arises whether in the Mn-free alloy system Co-Ni-Ga similar mechanisms are effective. In this context, we present first measurements of the ͓110͔ TA 2 phonons in Co 48 Ni 22 Ga 30 by means of inelastic neutron scattering. The results are related to first-principles calculations of the electronic structure, including Fermi surfaces as well as the full phonon dispersion of stoichiometric Co 2 NiGa within the framework of density-functional theory ͑DFT͒.…”
Section: Introductionmentioning
confidence: 99%
“…The non-modulated 2M-martensite is very attractive subject of inquiry because it corresponds to the ground state of these alloys [24] and shows a rather large magnetic field-induced strain of 0.2% [25]. Since the spontaneous lattice distortion during MT is almost as large as 20%, an actuation of huge strains is theoretically attainable under the different driving forces.…”
Section: Introductionmentioning
confidence: 99%